Impact of Dietary Oxidized Lipids on Energy Metabolism - Marc Pignitter; Veronika Somoza (Advances in Food Technology and Nutrition Sciences, 2015)
Consumption of dietary fat is known to influence metabolic rate and metabolic path-ways. Dietary intake of unoxidized polyunsaturated fatty acids was shown to lead to an in-creased metabolic rate. Identification of the underlying mechanism revealed that modifications of the energy metabolism are associated with modifications of membrane lipid composition leading to the membrane pacemaker theory of metabolism. Mitochondrial membranes were shown to adapt their lipids to the dietary fat composition. Dietary fat is commonly prepared by applying heat treatment to increase palatability. Heat treatment of food lipids result in the for-mation of oxidized lipids. Intake of oxidized lipids might affect energy metabolism in a differ-ent way than their corresponding unoxidized lipids. However, scientific literature of the effects of individual oxidized lipids found in heat-treated dietary fats on the energy metabolism rel-evant for metabolic syndrome, diabetes and obesity research is scarce. This review comprises current knowledge of the impact of unoxidized and oxidized lipids on the energy metabolism.